2005
DOI: 10.2527/2005.83112653x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of puberty in beef heifers fed high- or low-starch diets for different periods before breeding1

Abstract: Spring-born Hereford x Angus heifers (n = 206) were used to determine effects of energy supplementation programs and amount of starch in the diet on incidence of puberty. In Exp. 1, heifers (205 +/- 5 kg; n = 68) grazing dormant native pasture were fed 0.9 kg/d (as-fed basis) of a 42% CP supplement from November until February 14. Heifers were stratified by weaning weight and allotted randomly to treatment before breeding (May to July). Treatments were 1) 0.9 kg (as-fed basis) of a 42% CP supplement/d and past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
3
15
0
3
Order By: Relevance
“…The decreased percentage of EXT heifers being pubertal was likely the result of several factors including growth rate, winter diet, possibly monensin supplementation, which was a function of diet quality, and other behavioral and environmental factors differing in each development system. These data agree with recent literature indicating reduced postweaning ADG resulting from lower diet quality, with or without moderate realimentation before breeding, reduces the percentage of heifers attaining puberty (Granger et al, 1990;Lalman et al, 1993;Buskirk et al, 1995Buskirk et al, , 1996Marston et al, 1995;Lynch et al, 1997;Ciccioli et al, 2005;Gasser et al, 2006). Martin et al (2008) indicated reducing the percentage of mature BW at breeding by approximately 6% resulted in a nonsignificant, 17% decrease in percentage of pubertal heifers at breeding.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The decreased percentage of EXT heifers being pubertal was likely the result of several factors including growth rate, winter diet, possibly monensin supplementation, which was a function of diet quality, and other behavioral and environmental factors differing in each development system. These data agree with recent literature indicating reduced postweaning ADG resulting from lower diet quality, with or without moderate realimentation before breeding, reduces the percentage of heifers attaining puberty (Granger et al, 1990;Lalman et al, 1993;Buskirk et al, 1995Buskirk et al, , 1996Marston et al, 1995;Lynch et al, 1997;Ciccioli et al, 2005;Gasser et al, 2006). Martin et al (2008) indicated reducing the percentage of mature BW at breeding by approximately 6% resulted in a nonsignificant, 17% decrease in percentage of pubertal heifers at breeding.…”
Section: Resultssupporting
confidence: 91%
“…However, final pregnancy rate was not different (P = 0.38) between EXT and DL Nontraditional heifer development heifers. Nearly all previous research indicates postweaning BW gain restriction resulted in similar final pregnancy rates (Granger et al, 1990;Lalman et al, 1993;Buskirk et al, 1995;1996;Lynch et al, 1997;Funston and Deutscher, 2004;Ciccioli et al, 2005;Gasser et al, 2006;Martin et al, 2008). The percentage of heifers calving in the first 21 d was similar (P = 0.30; Table 7) between treatments and greater than 70% for the entire group, indicating heifers not becoming pregnant to AI became pregnant at the subsequent estrus.…”
Section: Resultsmentioning
confidence: 63%
“…Llewelyn et al (1992) studied indigenous African goats and observed that the return of ovarian activity after parturition occurred prior to improvement in body condition and weight. Furthermore, Ciccioli et al (2005) found in beef heifers that the response to oestrus synchronization in the first oestrus cycle in the postpartum period is not influenced by body Silva et al condition at parturition. In general, the CIDR-PGF2α hormone protocol is a highly efficient treatment in synchronizing oestrus in goats (Oliveira et al, 2001) and in postpartum cows (Lucy et al, 2001;Flores et al, 2006), demonstrating better efficiency in simulating corpus luteum function.…”
Section: Discussionmentioning
confidence: 95%
“…Heifers developed on pasture (36RUP and 50RUP) had greater (P < 0.01) ADG from the time of breeding to pregnancy diagnosis. Heifers developed on low-quality winter range may compensate for the minimal prebreeding ADG and gain more BW during the breeding season than heifers fed in a drylot due to decreased maintenance requirements and the ability to respond to a seasonal improvement in forage quality (Marston et al, 1995;Ciccioli et al, 2005).…”
Section: Methodsmentioning
confidence: 99%